1995
DOI: 10.1021/ja00148a002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of (2-Deoxy-.beta.-D-glucopyranosyl)pyridinium Salts

Abstract: The hydrolysis reactions of three (2-deoxy-/?-D-glucopyranosyl)pyridinium salts exhibit first-order rate constants that are independent of pH in the range of 4.4-10.1 pH units. Derived second-order rate constants for the hydrolysis reactions of (2-deoxy-/J-D-glucopyranosyl)-4'-bromoisoquinolinium bromide (5b) conducted in the presence of nucleophilic monoanions (µ = 2.0) including AcO-, Cl-, Br-, and N3-exhibit a Swain-Scott parameter (s) of 0.03 ± 0.05, indicating that these reactions show no sensitivity to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 0 publications
9
70
1
Order By: Relevance
“…The oxocarbenium is non-solvent equilibrated in light of the apparent necessity of a close approach of the methanol O m before its formation. This was previously found to be the case for many glucopyranoside hydrolysis reactions, [1][2][3] as well as for the theoretical study of glycosyltransferase. [46] double bond to the C 1 ÀO 5 single bond the O 5 site becomes again re-solvated.…”
Section: Discussionsupporting
confidence: 53%
“…The oxocarbenium is non-solvent equilibrated in light of the apparent necessity of a close approach of the methanol O m before its formation. This was previously found to be the case for many glucopyranoside hydrolysis reactions, [1][2][3] as well as for the theoretical study of glycosyltransferase. [46] double bond to the C 1 ÀO 5 single bond the O 5 site becomes again re-solvated.…”
Section: Discussionsupporting
confidence: 53%
“…These reactions are on the borderline between D N + A N (S N 1) and A N D N (S N 2) mechanisms (Scheme 2). [32][33][34] A previous semiempirical study of the gas-phase TS of nicotinamide riboside hydrolysis indicated a highly oxacarbenium-ion-like TS structure, which suggests the ability of semiempirical approaches to correctly describe this type of reactive system. [35] In this study, the gas-phase reaction is described by an oxacarbenium-ion-like TS structure with bond distances of C1ÀN (leaving group) and C1ÀO (incoming water group) of 2.13 and 2.45 , respectively (Figure 3 b).…”
Section: Gas-phase Calculationsmentioning
confidence: 99%
“…The overall energy profile of Figure 2 shows an activation energy of 20.66 kcal mol À1 for the NAD + hydrolysis reaction, for which an activation enthalpy of 25.2 kcal mol À1 has been estimated. [33] QM/MM calculations Figure 4 shows the ONIOM2 [31] (AM1/Dreiding)-optimized geometries of the NR-water reactant (Michaelis complex), transition state, and final product of the hydrolysis reaction at the PARP active site. In Figure 5, the energy profile along the reaction coordinate of the PARP-catalyzed NR hydrolysis (B3LYP/6-31 + G(d) single-point calculations on geometry optimized at the QM/MM level) is displayed and shows an activation energy of 7.26 kcal mol…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
See 2 more Smart Citations